Profile of hypertensive and / or diabetic patients of a Basic Health Unit in Maranhão, Brazil (Research, Society and Development, 2020)
Objective: to know the profile of hypertensive and / or diabetic patients treated at a basic health unit in Maranhão. Method: This is a descriptive, retrospective study with a quantitative approach, performed in April 2018, with data from medical records of 137 patients enrolled in the HIPERDIA program. Data were collected through a structured script and tabulated using the SPSS SamplePower Software. Results: in the researched unit there were 195 registered patients, hypertensive and / or diabetic. A higher number of female hypertensive and / or diabetic patients was observed, with a higher prevalence of these pathologies in individuals between 60 and 69 years, followed by those aged between 50 and 59. The predominant weight among participants was between 60 and 69kg. The main blood pressure values ​​found were